1999
DOI: 10.1164/ajrccm.160.3.9812110
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Severe Asthma Can Be Divided Pathologically into Two Inflammatory Subtypes with Distinct Physiologic and Clinical Characteristics

Abstract: The mechanisms associated with the development of severe, corticosteroid (CS)-dependent asthma are poorly understood, but likely heterogenous. It was hypothesized that severe asthma could be divided pathologically into two inflammatory groups based on the presence or absence of eosinophils, and that the inflammatory subtype would be associated with distinct structural, physiologic, and clinical characteristics. Thirty-four severe, refractory CS-dependent asthmatics were evaluated with endobronchial biopsy, pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
894
4
41

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,116 publications
(985 citation statements)
references
References 28 publications
31
894
4
41
Order By: Relevance
“…ASM hyperplasia is one of the irreversible structural changes that occur in the airways of asthmatic patients (56). Thickening of the airway wall, partially from ASM hyperplasia, has a potential contribution toward irreversible airway obstruction in patients with severe asthma (57). In the present study, we demonstrated that activin A increased the number and DNA synthesis of HASMC.…”
Section: Discussionsupporting
confidence: 62%
“…ASM hyperplasia is one of the irreversible structural changes that occur in the airways of asthmatic patients (56). Thickening of the airway wall, partially from ASM hyperplasia, has a potential contribution toward irreversible airway obstruction in patients with severe asthma (57). In the present study, we demonstrated that activin A increased the number and DNA synthesis of HASMC.…”
Section: Discussionsupporting
confidence: 62%
“…Several methods are being used to identify airway eosinophilia in the airways including bronchial biopsies, induced sputum, blood, and exhaled breath. Traditionally, airway biopsies or bronchoalveolar lavage is considered as the gold standard for assessing airway inflammation [15] but this method is too invasive for routine clinical use. Therefore, there has been great interest in methods to assess airway inflammation noninvasively and in a convenient and inexpensive way.…”
Section: Current Methods For Diagnosing Eosinophilic Asthmamentioning
confidence: 99%
“…Wenzel and colleagues first described this 'eosinophil high' severe asthma phenotype when performing bronchial biopsies and showed that it was associated with airway remodeling and risk of near-fatal asthma attacks [15]. Others showed that severe eosinophilic asthma is characterized by frequent exacerbations and often requires systemic corticosteroid treatment for control of the disease [14,16,17].…”
Section: How Is Eosinophilic Asthma Defined?mentioning
confidence: 99%
“…32,33 Normal controls had normal pulmonary function, if able to perform pulmonary function tests, and had no history of any respiratory illness. Normal patients were recruited from National Jewish and from Cincinnati Children's Hospital Medical Center bronchoalveolar lavage (BAL) specimen bank.…”
Section: Subjectsmentioning
confidence: 99%
“…Normal patients were recruited from National Jewish and from Cincinnati Children's Hospital Medical Center bronchoalveolar lavage (BAL) specimen bank. Cell free lavage fluid was obtained as previously described 32,33 and stored at −70°C until analysis. BAL fluid was analyzed for human IL-13Rα2 by using the DuoSet kit from R&D Systems (Minneapolis, Minn) according to the manufacturer's instructions.…”
Section: Subjectsmentioning
confidence: 99%